HUBUNGAN DEGRASI LINGKUNGAN DENGAN KEMISKINAN - Reswita Reswita; Gita Mulyasari; Reflis Reflis (Sekolah Tinggi Pariwisata Mataram, 2021)
Environmental degradation is a decrease in environmental quality due to development activities which are characterized by the non-functioning of environmental components or it can also be said that environmental degradation is a natural environmental condition that leads to damage to biodiversity and endangers environmental health. Environmental degradation is caused by two main factors, namely nature and humans. Land degradation can be in the form of damage to marine ecosystems, critical land, and forest damage. Land degradation is closely related to land, population density, and poverty. Poverty is a condition of living conditions that are lacking in meeting basic human needs. Community poverty is considered to be one of the factors that causes environmental damage. This paper aims to see whether there is a relationship between environmental degradation and poverty. The method used in the preparation of this paper is a literature study by reviewing several articles that have been published by previous researchers and take the essence of the research. From the literature study, it is concluded that there is a relationship between environmental degradation and poverty, but the cause of environmental degradation is not solely caused by poverty, but is mostly caused by human activities in utilizing the environment.